The Relationship Between Workload and Employee Work Productivity at PT Semesta Berkat Utama - Daya Indrawan; Said Salim Dahda; Deny Andesta (G-Tech: Jurnal Teknologi Terapan, 2026)
Employee productivity is a critical factor for organizational success in an increasingly competitive industrial environment. Workload is often perceived as a determinant that can influence productivity, with effects varying depending on individual adaptability and management support. This study aims to analyze the relationship between workload and employee productivity at PT Semesta Berkat Utama. A quantitative correlational approach with a cross-sectional design was applied, involving all 10 employees selected using a saturated sampling technique. Data were collected through closed questionnaires using a 5-point Likert scale and analyzed using Spearman rank correlation due to non-normal data distribution. The results show a very strong positive correlation between workload and productivity (r = 0.967, p = 0.000 < 0.05), indicating that higher workload is associated with higher productivity in this context. The coefficient of determination (r² = 0.991) suggests that workload explains 99.1% of productivity variance. These findings imply that high workload can act as a performance driver when supported by strong motivation and work commitment. The study provides practical insight for proportional workload management to sustain optimal productivity.